Pembelajaran Problem Solving disertai Media Bangun Ruang untuk Meningkatkan Hasil Belajar Matematika Siswa SMPN 1 Sukadana - Ummi Rosyidah (SAP (Susunan Artikel Pendidikan), 2017)
Education is a long term investment that requires effort, cooperation from all related parties and substantial funds to achieve improvement in the educational process. Therefore, it is necessary for teachers to choose an appropriate method, so that each material received is easy to accept and students are able to learn independently. One of alternatives, namely by using the method of ProblemSolving learning accompanied by geometry media on the materials of cube and cuboid. The purpose of this research is to improve students' mathematics learning outcomes through the use of problem solving learning method accompanied by mathematics geometry for students class VIII SMP Negeri 1 Sukadana. This study uses a classroom action research design. The subject of this research is 30 students of class VIII SMP Negeri 1 Sukadana. This study consists of two cycles, the learning result data obtained through the test results at each end of cycle. From the results of test, students who passed with KKM ? 65 in cycle I are 18 people or 60% and in the II cycle increase to 24 people or 80%. From the results of data analysis, it can be concluded the use of problem solving learning method accompanied by geometry media can improve students? learning outcomes on cube and cuboid materials.